Clinical Microbiology Laboratories' Adoption of Culture-Independent Diagnostic Tests Is a Threat to Foodborne-Disease Surveillance in the United States - Shea, Shari (J Clin Microbiol, 2016)
In November 2015, the Centers for Disease Control and Prevention (CDC) sent a letter to state and territorial epidemiologists, state and territorial public health laboratory directors, and state and territorial health officials. In this letter, culture-independent diagnostic tests (CIDTs) for detection of enteric pathogens were characterized as “a serious and current threat to public health surveillance, particularly for Shiga toxin-producing Escherichia coli (STEC) and Salmonella.” The document says CDC and its public health partners are approaching this issue, in part, by “reviewing regulatory authority in public health agencies to require culture isolates or specimen submission if CIDTs are used.” Large-scale foodborne outbreaks are a continuing threat to public health, and tracking these outbreaks is an important tool in shortening them and developing strategies to prevent them. It is clear that the use of CIDTs for enteric pathogen detection, including both antigen detection and multiplex nucleic acid amplification techniques, is becoming more widespread. Furthermore, some clinical microbiology laboratories will resist the mandate to require submission of culture isolates, since it will likely not improve patient outcomes but may add significant costs. Specimen submission would be less expensive and time-consuming for clinical laboratories; however, this approach would be burdensome for public health laboratories, since those laboratories would need to perform culture isolation prior to typing. Shari Shea and Kristy Kubota from the Association of Public Health Laboratories, along with state public health laboratory officials from Colorado, Missouri, Tennessee, and Utah, will explain the public health laboratories' perspective on why having access to isolates of enteric pathogens is essential for public health surveillance, detection, and tracking of outbreaks and offer potential workable solutions which will allow them to do this. Marc Couturier of ARUP Laboratories and Melissa Miller of the University of North Carolina will explain the advantages of CIDTs for enteric pathogens and discuss practical solutions for clinical microbiology laboratories to address these public health needs.